2011
DOI: 10.1038/jp.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional strategies and growth in extremely low birth weight infants with bronchopulmonary dysplasia over the past 10 years

Abstract: Objective: Changes in nutritional strategies over the past decade have been shown to improve postnatal growth in extremely low birth weight (ELBW) infants. We showed 10 years ago that the majority of these ELBW infants with bronchopulmonary dysplasia (BPD) suffer postnatal growth failure. We theorized that recent changes in nutritional support strategies would positively affect growth outcomes in ELBW infants with BPD.Study Design: A retrospective study of 88 ELBW infants with BPD. Nutritional data, postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
2
21
1
1
Order By: Relevance
“…Our results are consistent with previously published data [19, 20] indicating that improved nutritional strategies can positively affect the growth of pre-term infants with BPD, who frequently suffer from post-natal growth retardation [6, 21]. Madden et al [19] found a significant increase in mean weight z-scores and a decrease in the proportion of infants with a mean weight z-score of <2 SD at 20 months of corrected age in a cohort of extremely low gestational age infants with BPD born in 2000-2003 in comparison with a cohort of extremely low gestational age infants with BPD born in 1996-1999.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are consistent with previously published data [19, 20] indicating that improved nutritional strategies can positively affect the growth of pre-term infants with BPD, who frequently suffer from post-natal growth retardation [6, 21]. Madden et al [19] found a significant increase in mean weight z-scores and a decrease in the proportion of infants with a mean weight z-score of <2 SD at 20 months of corrected age in a cohort of extremely low gestational age infants with BPD born in 2000-2003 in comparison with a cohort of extremely low gestational age infants with BPD born in 1996-1999.…”
Section: Discussionsupporting
confidence: 94%
“…The authors speculated that the improvement in the growth outcomes may have been due to changes in the infants’ nutritional management, such as the use of more aggressive parenteral nutrition and more caloric post-discharge formulae. Theile et al [20] retrospectively studied 88 extremely low birth weight infants with BPD, and found a reduction in post-natal growth retardation at the time of hospital discharge (as assessed on the basis of weight and head circumference) in infants fed caloric-dense milk. However, as we found that the improved weight gain in the infants belonging to the intervention group was not associated with an improvement in length gain, there may be some concern about the quality of their growth because, although accompanied by the provision of a sufficient protein intake, the increased caloric intake may have caused relatively greater fat deposition [22].…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] However, in our cohort there were no overall growth differences at 36 weeks PMA between infants with no/mild BPD and infants with moderate/severe BPD. In the infants born < 26 weeks GA who developed moderate/severe BPD, we observed that length and head circumference growth lagged behind the infants who had no/mild BPD.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, they tried to verify if increased rates of protein administration during the first month of life could achieve higher growth rates, as has been suggested previously (52). The literature is at significant variance here, in that earlier and subsequent trials have shown that both positive effects upon growth and no effects when protein/amino acid supplementation have been increased (53). In addition, certain amino acids and amino acid acylcarnitines (e.g., isovalerylcarnitine) were elevated to levels that were of concern, while other amino acid levels (e.g., alanine) appeared to be inadequate.…”
Section: Nutritional Considerationsmentioning
confidence: 96%